Internet use and e-health literacy among tuberculosis patients in the Directly Observed Therapy Centre, Lagos State, Nigeria - Olalekan Moses Olayemi; Timothy Shola Abolarinwa (Information Research: An International Electronic Journal)
Introduction. This study investigated Internet use and e-health literacy among tuberculosis patients attending Directly Observed Therapy Centre in Lagos State, Nigeria.